2022
DOI: 10.3390/ijerph19094961
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Matrix Type on Marginal Gap Formation of Deep Class II Bulk-Fill Composite Restorations

Abstract: Background: To test the hypothesis that transparent matrices result in more continuous margins of bulk-fill composite (BFC) restorations than metal matrices. Methods: Forty standardized MOD cavities in human molars with cervical margins in enamel and dentin were created and randomly assigned to four restorative treatment protocols: conventional nanohybrid composite (NANO) restoration (Tetric EvoCeram, Ivoclar Vivadent, Schaan, Liechtenstein) with a metal matrix (NANO-METAL) versus transparent matrix (NANO-TRAN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…A tight‐fitting matrix facilitates the provision of direct restorations with excellent marginal adaptation. Circumferential metal matrices, the type of matrix most used in the studies included in this review, were shown to have a positive influence on the marginal quality of deep class II RBC restorations 59 . Such matrices may therefore be regarded as the matrix system of choice for DME.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A tight‐fitting matrix facilitates the provision of direct restorations with excellent marginal adaptation. Circumferential metal matrices, the type of matrix most used in the studies included in this review, were shown to have a positive influence on the marginal quality of deep class II RBC restorations 59 . Such matrices may therefore be regarded as the matrix system of choice for DME.…”
Section: Discussionmentioning
confidence: 99%
“…Circumferential metal matrices, the type of matrix most used in the studies included in this review, were shown to have a positive influence on the marginal quality of deep class II RBC restorations. 59 Such matrices may therefore be regarded as the matrix system of choice for DME. However, it is often tricky to achieve a good marginal seal with a matrix in proximal defects extending beyond the CEJ.…”
Section: Sequence Of Restorative Procedures In In Vitro/in Silico Stu...mentioning
confidence: 99%
“…The isolation of the working field, a matrix that tightly seals the margin of the subgingival defect, and precision during all working steps involved in the bonding and buildup procedure are essential for DME [ 1 ]. When conventional RBC is used, metal matrixes—like the ones applied in the present study—are superior to transparent matrixes, and adequate light polymerization, including light curing from three sides after matrix removal, needs to be ensured [ 25 ]. Such details of the restorative procedure of a direct RBC must be taken into consideration along with clinical and radiographic indicators of restoration integrity when one assesses the suitability of an existing RBC restoration for DME.…”
Section: Discussionmentioning
confidence: 99%
“…Data of a recent laboratory study suggest that bulk fill RBC with more efficient photo initiators achieves a better marginal quality in proximal boxes below the CEJ compared with conventional RBC [ 25 ]. Accordingly, bulk fill RBCs promise to be an equivalent or superior alternative to conventional RBCs even though the marginal quality of DME restorations made with conventional RCB was rated favorably at every time point in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…There are a wide variety of matrix systems on the market that are designed for posterior direct resin composite restorations. The two most frequently used are the circumferential and sectional matrix systems [23,24] . In 1871, the circumferential matrix band was first introduced by Dr. Louis Jack.…”
Section: Introductionmentioning
confidence: 99%